The Neoproterozoic Ediacaran Kaijiang-Xuanhan paleo-uplift in the Sichuan Basin, Western China - Guo, Ran; Li, Zeqi; Wu, Jianxue; Liu, Shugen; Sun, Wei; Wang, Peng; Deng, Bin; You, Liwei; Liu, Zhiyi (Frontiers in Earth Science, 2025)
The structural characteristics and formation evolution of the Sinian Kaijiang-Xuanhan paleo-uplift play a foundational role in the formation and evolution of the Sichuan Basin. To comprehensively understand the structural characteristics and formation evolution of the Sinian Kaijiang-Xuanhan paleo-uplift, this paper, based on geological, logging, seismic, and drilling, further confirms the existence of the Sinian Kaijiang-Xuanhan paleo-uplift and provides a detailed study of its characteristics. The entire Ediacaran tectonic sedimentary framework of the Sichuan Basin was controlled by this northeast-trending paleouplifted area. The Dengying Formation in the Kaijiang-Xuanhan region and the Mianyang-Anyue-Changning region both exhibit a thinning trend, but the genetic mechanisms are different. The thinning in the former is the result of sedimentary control during the early stages of paleouplift, with the lower parts of the first and second stages being absent; in the latter region, this is due to subsequent erosion. During the deposition periods of the Doushantuo and Dengying formations, the Sichuan Basin was predominantly in a weak compressional state, forming the Kaijiang-Xuanhan paleo-uplift, with the main structural orientation being northeastward. By the late Dengying Formation and early Cambrian, the region experienced a weak extensional state, resulting in the development of the Mianyang-Changning rift, with the main structural orientation being north-northwestward. The Kaijiang-Xuanhan paleo-uplift underwent four stages: the incubation period (before the deposition of the Doushantuo Formation), the peak development period (during the deposition of the Doushantuo Formation), the decline period (during the deposition of the Dengying Formation), and the extinction period (during the Lower Cambrian deposition). The further confirmation and in-depth study of the Sinian Kaijiang-Xuanhan paleo-uplift enhances the understanding of the Neoproterozoic craton of the Sichuan Basin and enriches the theory of the formation and evolution of the Sichuan Basin.